2018
DOI: 10.1530/joe-18-0335
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal undernutrition affects the phenotypes of PCOS model rats

Abstract: Although polycystic ovary syndrome (PCOS) is among the most common endocrine disorders in women of reproductive age, its etiology remains poorly understood. From the perspective of developmental origins of health and disease, some studies have investigated the relationship between low birth weight and the prevalence of PCOS and/or PCOS phenotypes in humans; however, the results of these studies were inconclusive. Here, we evaluated the effects of prenatal undernutrition on the metabolic and reproductive phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…Most women with PCOS show enlarged ovaries and PCO, 4 , 14 whereas DHT‐induced PCOS model rats show low ovarian weights and do not always exhibit an increased number of cystic follicles. 9 , 10 , 11 , 12 , 13 In addition, in our preliminary examination it was confirmed that DHT‐induced PCOS model rats had low uterine weights. It is possible that these phenotypic discrepancies between human patients and animal models may hamper the evaluation of the pathophysiology of PCOS at the systemic level.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Most women with PCOS show enlarged ovaries and PCO, 4 , 14 whereas DHT‐induced PCOS model rats show low ovarian weights and do not always exhibit an increased number of cystic follicles. 9 , 10 , 11 , 12 , 13 In addition, in our preliminary examination it was confirmed that DHT‐induced PCOS model rats had low uterine weights. It is possible that these phenotypic discrepancies between human patients and animal models may hamper the evaluation of the pathophysiology of PCOS at the systemic level.…”
Section: Introductionsupporting
confidence: 65%
“…Usually, DHT pellets or silicon tubes containing crystalline DHT are used to produce DHT‐induced PCOS animal models. 9 , 10 , 11 , 13 However, we suspected that these procedures may result in DHT having supra‐physiological effects on tissues and organs, and may induce some of the phenotypic discrepancies observed between PCOS animal models and human PCOS, such as small ovaries and uteri. On the contrary, it has been well established that the implantation of a silicon tube containing oil‐dissolved estradiol can reproduce the physiological hormonal milieu in female rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Letrozole treated adult female mice revealed an increased neuronal activation of Kiss1 (30). A DHT induced PCOS rat model resulted in decreased kiss1 gene expression, but the serum levels of testosterone, estradiol, LH, FSH were unaltered (31). Interestingly, in a letrozole induced PCOS model in adult rats, increased positivecell number of kisspeptin in the arcuate and decreased number of positive kisspeptin in anteroventral periventricular (AVPV) nucleus were reported (32).…”
Section: Discussionmentioning
confidence: 98%
“…Letrozole treated adult female mice revealed an increased neuronal activation of Kiss1 (60). A DHT induced PCOS rat model resulted in decreased kiss1 gene expression, but the serum levels of testosterone, estradiol, LH, FSH were unaltered (61). Interestingly, in a letrozole induced PCOS model in adult rats, increased positivecell number of kisspeptin in the arcuate and decreased number of positive kisspeptin in anteroventral periventricular (AVPV) nucleus were reported (62).…”
Section: Discussionmentioning
confidence: 98%